Improved separation performance of polyamide based reverse osmosis membrane incorporated with poly(dopamine) coated carbon nanotubes. Issue 32 (7th April 2021) - Zhang, Na; Yan, Tingting; Li, Chunhui; Deng, Huining; Li, Zhenhua; Yu, Ru; Wang, Tiejun; Xu, Shicai; Li, Qiang; Wang, Jihua
Abstract: A series of polyamide thin‐film nanocomposite (PA TFN) membranes have been fabricated by incorporating hydrophilic poly(dopamine) (PDA) coated carbon nanotubes (CNTs@PDA) into the PA selective layer via interfacial polymerization. The effects of PDA coating thickness on surface characteristics and separation performances of membranes are studied in detail. The PDA coating makes the surface of PA TFN membrane more hydrophilic, smoother and less electronegative. The desalination performance is obviously influenced by the coating thickness of PDA and the loading concentration of PDA@CNTs. The water fluxes of PDA@CNTs incorporated PA TFN membranes have been improved without sacrificing NaCl rejections. When the loading concentration is 0.0010%, the maximum water flux is 48.1 L m −2 h increasing by 45% compared with that of pristine PA membrane. Meanwhile, the NaCl rejection is up to 99.8%. The CNTs@PDA incorporated PA TFN membranes exhibit better anti‐fouling property and separation performance durability. This work proves that CNTs@PDA has great potential application in PA TFN membranes. Abstract :